ผลของการสอนวิทยาศาสตร์ตามแนวคิดวิทยาศาสตร์ เทคโนโลยีและสังคมที่มีต่อผลสัมฤทธิ์ในการเรียนวิทยาศาสตร์ของนักเรียนชั้น ประถมศึกษาปีที่ 6 - เนตรนุช พงศ์ศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research was to investigate effects of science teaching based on science, technology and society approach on science learning achievement of Prathom Suksa six students. The subjects were 38 Prathom Suksa six students from Chumchon Ban Photak School under the jurisdiction of the office of Sakolnakhon Provincial primary education, consisting of 19 students in experimental group and 19 students in the control group. The research instruments were science knowledge test, science process skill test, science attitude test and communication skill test. The experiment duration was 12 weeks. Data were analyzed by using mean, standard deviation, and t-test. The results were as follow : 1. The post-test arithmetic mean score of science knowledge of students taught by the science, technology and society was higher than the students taught by the contemporary method at .05 level of significance. 2. The post-test arithmetic mean score of science process skill of students taught by the science, technology and society was higher than the students taught by the contemporary method at .05 level of significance. 3. The post-test arithmetic mean score of science attitude of students taught by the science, technology and society was higher than the students taught by the contemporary method at .05 level of significance. 4. The post-test arithmetic mean score of communication skill of students taught by the science, technology and society was higher than the students taught by the contemporary method at .05 level of significance.